IMPORTANCE OF CASE STUDY METHOD IN LEARNING ENGLISH LANGUAGE - Robiya Malikova; Shahribonu Sirojiddinovna (Journal of new century innovations, 2023)
Abstract: the article examines the notion potential of using the case study teaching method as one of the innovative ways of teaching English as a second language to high school students. The case study method contributes to the formation and development of systemic, conceptual knowledge, analytical thinking, communication skills, as well as the skills of structuring information presented to students and establishing cause-and-effect relationships in senior schoolchildren.